What works for jetlag? A systematic review of non-pharmacological interventions. (February 2019) - Bin, Yu Sun; Postnova, Svetlana; Cistulli, Peter A.
Summary: Jetlag is a combination of travel fatigue and circadian misalignment resulting from air travel across time zones. Routinely recommended interventions based on circadian science include timely exposure to light and darkness (scheduled sleep), but the real-world effectiveness of these and other non-circadian strategies is unknown. We systematically reviewed the evidence for non-pharmacological interventions for jetlag. PubMed, EMBASE, Scopus, and Web of Science were searched. Studies reviewed 1) involved human participants undergoing air travel with a corresponding shift in the external light–dark cycle; 2) administered a non-pharmacological intervention; 3) had a control or comparison group; and 4) examined outcomes such as jetlag symptoms, sleep, cognitive/physical performance, mood, fatigue, or circadian markers. Thirteen studies used light exposure, physical activity, diet, chiropractic treatment, or a multifaceted intervention to counteract jetlag. Nine studies found no significant change in the outcomes, three reported mixed findings, and one was positive. The null findings are likely due to poorly designed circadian interventions and neglect of contributors to travel fatigue. Higher quality studies that schedule darkness as well as light, in the periods before, during, and after flight are needed to reduce the circadian component of jetlag. Interventions should also address the stressors that contribute to travel fatigue.